Structural and mechanistic characterization of bifunctional heparan sulfate N-deacetylase-N-sulfotransferase 1 - Mycroft-West, Courtney J.; Abdelkarim, Sahar; Duyvesteyn, Helen M. E.; Gandhi, Neha S.; Skidmore, Mark A.; Owens, Raymond J.; Wu, Liang (Nature communications, 2024)
Heparan sulfate (HS) polysaccharides are major constituents of the extracellular matrix, which are involved in myriad structural and signaling processes. Mature HS polysaccharides contain complex, non-templated patterns of sulfation and epimerization, which mediate interactions with diverse protein partners. Complex HS modifications form around initial clusters of glucosamine-N-sulfate (GlcNS) on nascent polysaccharide chains, but the mechanistic basis underpinning incorporation of GlcNS itself into HS remains unclear. Here, we determine cryo-electron microscopy structures of human N-deacetylase-N-sulfotransferase (NDST)1, the bifunctional enzyme primarily responsible for initial GlcNS modification of HS. Our structures reveal the architecture of both NDST1 deacetylase and sulfotransferase catalytic domains, alongside a non-catalytic N-terminal domain. The two catalytic domains of NDST1 adopt a distinct back-to-back topology that limits direct cooperativity. Binding analyses, aided by activity-modulating nanobodies, suggest that anchoring of the substrate at the sulfotransferase domain initiates the NDST1 catalytic cycle, providing a plausible mechanism for cooperativity despite spatial domain separation. Our data shed light on key determinants of NDST1 activity, and describe tools to probe NDST1 function in vitro and in vivo. Heparan sulfate biosynthesis is a complex process involving multiple reactions that extend and modify the polysaccharide. Here, the authors resolve structures of NDST1, responsible for the critical N-sulfoglucosamine modification of heparan sulfate.